2021
DOI: 10.1161/jaha.120.019788
|View full text |Cite
|
Sign up to set email alerts
|

Does the Age of Sudden Cardiac Death in Family Members Matter in Brugada Syndrome?

Abstract: Background Brugada syndrome is an inherited cardiac channelopathy associated with major arrhythmic events (MAEs). The presence of a positive family history of sudden cardiac death (SCD) as a risk predictor of MAE remains controversial. We aimed to examine the association between family history of SCD and MAEs stratified by age of SCD with a systematic review and meta‐analysis. Methods and Results We searched the databases of MEDLINE and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…However, a meta-analysis of 22 studies involving 3386 patients found that history of SCD in family members <40 years of age doubled the risk for a major arrhythmic event. 140…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…However, a meta-analysis of 22 studies involving 3386 patients found that history of SCD in family members <40 years of age doubled the risk for a major arrhythmic event. 140…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…However, a meta-analysis of 22 studies involving 3386 patients found that history of SCD in family members <40 years of age doubled the risk for a major arrhythmic event. 209…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…JWS is related to vulnerability for the development of SCD, pVT and VF in patients with structurally normal hearts [24,25]. A meta-analysis by Rattanawong et al [26] found that a family history of SCD in BrS patients less than 40 years of age doubled the risk of a major arrhythmic event (MAE). Previous reports also suggested the family history of SCD in ERS ranges from 13% to 18% [27,28].…”
Section: Discussionmentioning
confidence: 99%